Temporal Responses of Spontaneous Plant Community Diversity to Sowing Density of Cultivated Herbs in Park Greenspaces - Wu, Yuyan (International Journal of Natural Resources and Environmental Studies, 2026)
Understanding how sowing density influences spontaneous plant communities over time is critical for optimizing vegetation management in urban park greenspaces. This study investigated the temporal responses of spontaneous plant community diversity to varying sowing densities of cultivated herbs in Hangzhou, China. A semi-controlled field experiment was conducted using three sowing densities (20, 100, and 200 plants m⁻²), and spontaneous plant communities were monitored monthly from December to May. Diversity was assessed using the Shannon–Wiener index, Pielou’s evenness index, and Margalef’s richness index, and the data were analyzed with linear mixed-effects models. Spontaneous plant diversity exhibited clear seasonal dynamics, with diversity indices increasing from winter to spring and peaking in March–April. The effects of sowing density were strongly time-dependent. Differences among density treatments were relatively small during the initial stages but became more pronounced during the spring growth period. Specifically, medium and high densities were associated with lower diversity and species richness during the peak period. In contrast, evenness was primarily influenced by temporal variation rather than sowing density. Community composition varied among treatments, mainly through shifts in species abundance rather than species turnover. These findings indicate that sowing density can serve as a practical tool for regulating spontaneous plant diversity and highlight March–April as a key period for management interventions in park greenspaces.